Some fatigue crack problems in engineering structures with stress concentration - Muhammad Rafee Yahya (Nanyang Technological University, 2020)
The advancements in technology pushes humans to create more advanced machinery and structures to ease the lives of the general population. These advanced machineries and structures include everything from aircraft, to get people from one end of the world to the other, as well as skyscrapers that go higher and higher into the skies to solve the problem of ground space. One thing that all of them share in common is that they are highly reliant on their ability to maintain their structure. A major influence in the strength of a structure is the material chosen to become the foundation of that structure. With that, it is very important to understand the behaviour of materials when subjected to loads that may cause catastrophic failure. At most times, there are behavioural signs that appear before a catastrophic failure occurs. One of those signs are cracks. Based on the location of those cracks, structures may fail in a multitude of patterns. The purpose of understanding the behaviour of the materials with cracks and under loads is to allow for more methods to prevent such an event from occurring and also to control the situation if the material decides to fail. Thus, the study of fracture mechanics comes into the picture. This report will document the results of two locations of cracks and the material behaviour, using the Finite Element Analysis software, ANSYS. These cracks will be simulated in 2-D using the software and the results obtained will be contrasted with the theoretical formula for the relevant cracks based on fracture mechanics concepts.